2019
DOI: 10.3390/ijms20133308
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Enhances Nomegestrol Acetate Suppressing Growth of Endometrial Cancer Cells and May Correlate to Downregulating mTOR Activity In Vitro and In Vivo

Abstract: This study investigated the effect of a novel progestin and its combination with metformin on the growth of endometrial cancer (EC) cells. Inhibitory effects of four progestins, including nomegestrol acetate (NOMAC), medroxyprogesterone acetate, levonorgestrel, and cyproterone acetate, were evaluated in RL95-2, HEC-1A, and KLE cells using cell counting kit-8 assay. Flow cytometry was performed to detect cell cycle and apoptosis. The activity of Akt (protein kinase B), mTOR (mammalian target of rapamycin) and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 51 publications
1
13
0
Order By: Relevance
“…Metformin has also been shown to have a synergistic impact on progesterone's inhibitory effect on endometrial cell proliferation. [9][10][11] Growing evidence in the literature suggests that metformin may be a beneficial adjunctive therapy, with a synergistic effect alongside progestin, in the suppression of endometrial proliferation.…”
Section: Highlightsmentioning
confidence: 99%
“…Metformin has also been shown to have a synergistic impact on progesterone's inhibitory effect on endometrial cell proliferation. [9][10][11] Growing evidence in the literature suggests that metformin may be a beneficial adjunctive therapy, with a synergistic effect alongside progestin, in the suppression of endometrial proliferation.…”
Section: Highlightsmentioning
confidence: 99%
“…In an in vitro study, metformin delayed and prevented the IGF-1R feedback-induced proliferation of EC cells, with high concentrations of metformin markedly promoting the apoptosis of EC cells (67). In an in vivo study, the intraperitoneal injection of metformin markedly reduced the circulating IGF-1 levels in mice and strongly inhibited the development of xenograft tumors (75). In addition to suppressing the proliferation-promoting effect of IGF-1 and IGF-2, metformin has also been shown to increase progesterone receptor expression, which appears to be beneficial in the treatment of EC (72).…”
Section: Metformin Directly Inhibits the Development Of Ecmentioning
confidence: 97%
“…Multiple in vitro studies with USC cell lines demonstrated that metformin inhibited cell proliferation and metastasis via inhibiting oxidative phosphorylation (OXPHOS) and ATP consumption, further activating AMPK to suppress its downstream targets such as the mTOR and STAT3 pathways [46]. Other important signaling pathways were also identified, such as PI3K/AKT/mTOR and MAPK/ERK [46,47]. Several clinical trials and case reports of metformin treatment as a single agent or combination with other treatments have been established; for example, a phase II/III trial will add metformin or placebo to paclitaxel/carboplatin as the first-line therapy for advanced EC (NCT02065687) [45,48].…”
Section: Mitochondrial Functionmentioning
confidence: 99%